ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC MEREK HONDA VARIO - Kusmanto Kusmanto; Sri Muryanti (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This study aims to determine the effect of brand image, advertising, and product quality on purchasing decisions of Honda Vario brand automatic motorcycles. The method used in this study is a quantitative method with several classical assumption tests and multiple regression analysis. Based on the results of hypothesis testing, it is obtained that the brand image variable (X1) partially influences the purchase decision variable (Y) with a t-count value of 11,662 greater than the t-value of 1,658 and a significant value of 0.000. The advertising variable (X2) partially influences the purchase decision variable (Y) with a t-test value of 3,881, greater than the t-table value of 1,658 and a significant value of 0,000. The product quality variable (X3) partially also influences the purchasing decision variable (Y) with a t-test value of 9,732, greater than the t-table value of 1,658 and a significant value of 0,000. Simultaneously brand image variables (X1), advertisements (X2) and product quality (X3) influence the purchase decision variable (Y) with an F-calculated value of 332,812 greater than the F value of table 3,08 and a significant value of 0,000. variable brand image (X1), advertising (X2) and product quality (X3) have a contribution in influencing the purchase decision variable (Y) of 90,0%. While the remaining 10,0% is influenced by other variables not included in this study. From the conclusions above, suggestions can be given to companies that companies need to maintain and improve product quality.